2016
DOI: 10.3402/ejpt.v7.30165
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the PTSD Checklist for DSM-5: a pilot study

Abstract: BackgroundTo date there is a lack of studies assessing the psychometric properties of the recently revised PTSD Checklist (PCL), the PTSD Checklist for DSM-5 (PCL-5). The aim of this pilot study was to examine the psychometric properties of the PCL-5 in parents of children with burns.MethodsThe participating parents (N=62, mean age=38) completed self-report questionnaires, 0.8–5.6 years after their child's burn. Measures were the PCL-5, the Impact of Event Scale-Revised (IES-R), the Montgomery–Åsberg Depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(123 citation statements)
references
References 22 publications
9
113
1
Order By: Relevance
“…Regarding internal consistency, in line with previous studies in other cultures, the Brazilian PCL-5 has shown excellent Cronbach's alpha values (Ashbaugh et al, 2016;Blevins et al, 2015;Bovin et al, 2016;Krüger-Gottschalk et al, 2017;Price et al, 2016;Sveen et al, 2016;Verhey et al, 2018;Wortmann et al, 2016). The internal consistency of the independent clusters was also adequate, with Cronbach's alpha values ranging from .87 to .90.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Regarding internal consistency, in line with previous studies in other cultures, the Brazilian PCL-5 has shown excellent Cronbach's alpha values (Ashbaugh et al, 2016;Blevins et al, 2015;Bovin et al, 2016;Krüger-Gottschalk et al, 2017;Price et al, 2016;Sveen et al, 2016;Verhey et al, 2018;Wortmann et al, 2016). The internal consistency of the independent clusters was also adequate, with Cronbach's alpha values ranging from .87 to .90.…”
Section: Discussionsupporting
confidence: 84%
“…Previous investigations on the psychometric properties of the PCL-5 in other cultures have demonstrated excellent psychometric validity and reliability of the instrument (Ashbaugh, Houle-Johnson, Herbert, El-Hage, & Brunet, 2016;Blevins, Weathers, Davis, Witte, & Domino, 2015;Bovin et al, 2016;Krüger-Gottschalk et al, 2017;Sveen, Bondjers, & Willebrand, 2016;Verhey, Chibanda, Gibson, Brakarsh, & Seedat, 2018;Wortmann et al, 2016). Preliminary findings on cutoff scores have presented mixed results, with suggested cutoff points ranging from 31 to 38 (Ashbaugh et al, 2016;Blevins et al, 2015;Bovin et al, 2016;Krüger-Gottschalk et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Initial evaluations of the instrument indicate that it has good test-retest reliability, convergent and discriminant validity (Blevins et al, 2015). The Swedish version was developed using a standard back-translation process and show satisfactory psychometric properties (Sveen, Bondjers, & Willebrand, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Total severity scores are calculated as the sum of individual items (range = 0-80). The PCL-5 has been shown to have good validity and reliability (Sveen, Bondjers, & Willebrand, 2016;Weathers, Litz, et al, 2013). Participants were instructed to complete the PCL-5 with respect to the index event identified in the trauma history interview.…”
Section: Modified Life Events Checklist For Diagnostic and Statistimentioning
confidence: 99%